2009
DOI: 10.1103/physrevlett.103.047401
|View full text |Cite
|
Sign up to set email alerts
|

Collective Magnetic Excitations in the Spin LadderSr14Cu24O41Measured Using High-Resolution Resonant Inelastic X-Ray Scattering

Abstract: We investigate magnetic excitations in the spin-ladder compound Sr 14 Cu 24 O 41 using high-resolution Cu L 3 edge resonant inelastic x-ray scattering (RIXS). Our findings demonstrate that RIXS couples to two-triplon collective excitations. In contrast to inelastic neutron scattering, the RIXS cross section changes only moderately over the entire Brillouin zone, revealing high sensitivity also at small momentum transfers, allowing determination of the two-triplon energy gap as 100 AE 30 meV. Our results are ba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
121
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(131 citation statements)
references
References 35 publications
10
121
0
Order By: Relevance
“…S3). This observation is representative for single-magnon excitations as revealed with Cu L 3 RIXS for many cuprates 11,[16][17][18][19] . Unlike the parent cuprates, which are long-range ordered AF Mott insulators, the Fe-pnictide parent compounds are AF ordered spin-density wave semi-metals with compensating electron-and hole-like Fermi-surface pockets involving several Fe 3d orbitals.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…S3). This observation is representative for single-magnon excitations as revealed with Cu L 3 RIXS for many cuprates 11,[16][17][18][19] . Unlike the parent cuprates, which are long-range ordered AF Mott insulators, the Fe-pnictide parent compounds are AF ordered spin-density wave semi-metals with compensating electron-and hole-like Fermi-surface pockets involving several Fe 3d orbitals.…”
Section: Resultssupporting
confidence: 57%
“…To measure spin excitations in parent BFA and superconducting BKFA Fepnictide samples, we employ RIXS, which has recently been established as a powerful probe of the dispersion of magnetic excitations in a wide energy-momentum window. Many studies on undoped parent cuprates have demonstrated the sensitivity of RIXS to single-magnon excitations 11,[16][17][18][19][20][21] and collective orbital excitations 17 . Doped superconducting cuprates exhibit intense paramagnons, damped spin excitations over much of the BZ with dispersions and spectral weights closely similar to those of magnons in undoped AF ordered parent systems 11,19 .…”
Section: Resultsmentioning
confidence: 99%
“…Recent examples of RIXS studies of spin excitations include cuprates [6][7][8][9][10][11][12][13][14][15][16][17], iron-based superconductors [18] or iridates [19], where the intrinsic energy scale of the spin dynamics exceeds 100 meV. Initial RIXS data on the dispersion of magnons in the antiferromagnetic "parent compounds" of the cuprate high-temperature superconductors are fully consistent with prior INS data [6,12].…”
Section: Pacs Numbersmentioning
confidence: 61%
“…Although RIXS by nature has the ability to measure elementary excitations for numerous materials, it has shown an especially strong ability for characterizing elementary excitations in transition-metal oxides which manifest strong correlations [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. In particular, RIXS has been shown to be quite useful for the study of high-temperature superconducting materials: As magnetic fluctuations were proposed as candidates for the superconducting pairing glue, obtaining their dispersion relation can be crucial for unraveling the mystery of high T c [22].…”
Section: When ∼10mentioning
confidence: 99%